An investigation into the processes used in the production of printed health messages in South Africa - Maritha Snyman; Cecilia Penzhorn (Communicare)
Effective communication processes that include and invite audience participation are crucial for quality health care in a country. In South Africa the importance of this has been an issue of considerable discussion and debate. Critics have pointed out that many of the printed health messages and health communication campaigns that use the printed medium in South Africa are ineffective. To a great extent this failure is ascribed to the lack of audience involvement in the development and production of such messages. This article reports on an investigation undertaken to examine the extent of this problem. The processes used to develop and produce printed mass media health communication messages in South Africa are investigated by means of an in-depth exploration of the literature discussing and evaluating the production of health messages. This is complemented by an empirical exploration of selected printed messages covering a wide range of issues. Little evidence was found in the study of the reciprocal nature of communication where producers and communicators of health messages engage in sustained dialogue with their target audiences. The conclusion is drawn that audience participation is not the norm in the production processes of printed mass media health messages in South Africa.